(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study aims at understanding the gender difference in work life balance among college teachers. A sample of 180 teachers 90 male and 90 female from various colleges of bengaluru were administered with work life balance scale developed by Uday Pareek Joshi to know the work life balance index of college teachers. Null hypothesis was formulated and the obtained results were statistically analyzed using independent samples ‘t’ tests. The obtained ‘t’ scores on work life balance index indicated that there is no significant difference between both the group, indicating there is no gender difference in perception of work life balance among the college teachers.